2021
DOI: 10.3389/fphys.2021.737709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Fat Loss—Energetic Perspectives and the Role of Improved Adipose Tissue Function and Body Fat Distribution

Abstract: In obesity, excessive abdominal fat, especially the accumulation of visceral adipose tissue (VAT), increases the risk of metabolic disorders, such as type 2 diabetes mellitus (T2DM), cardiovascular disease, and non-alcoholic fatty liver disease. Excessive abdominal fat is associated with adipose tissue dysfunction, leading to systemic low-grade inflammation, fat overflow, ectopic lipid deposition, and reduced insulin sensitivity. Physical activity is recommended for primary prevention and treatment of obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 136 publications
1
33
0
Order By: Relevance
“…Accordingly, it has been reported that energy expenditures during low-volume exercise modalities, including LOW-HIIT [ 71 ], 1-RT [ 72 ] and WB-EMS [ 73 ], are quite small, ranging around 120–150 kcal per exercise session. However, it has also been documented that HIIT exercises are particularly effective to stimulate excess post-exercise oxygen consumption (EPOC), a valid measure to quantify elevated energy expenditure after cessation of exercise, which has been associated with higher fat loss over a longer period of time [ 74 , 75 , 76 ]. Furthermore, it has recently been shown that both HIIT and traditional RT resulted in increased resting metabolic rate for at least 14 h post-exercise in healthy women [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been reported that energy expenditures during low-volume exercise modalities, including LOW-HIIT [ 71 ], 1-RT [ 72 ] and WB-EMS [ 73 ], are quite small, ranging around 120–150 kcal per exercise session. However, it has also been documented that HIIT exercises are particularly effective to stimulate excess post-exercise oxygen consumption (EPOC), a valid measure to quantify elevated energy expenditure after cessation of exercise, which has been associated with higher fat loss over a longer period of time [ 74 , 75 , 76 ]. Furthermore, it has recently been shown that both HIIT and traditional RT resulted in increased resting metabolic rate for at least 14 h post-exercise in healthy women [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing energy consumption, increasing energy expenditure, and increasing muscle mass hold promise in the management of obesity and associated complications [ 19 , 20 ]. However, the effects of regular exercise training to manage obesity and related diseases are related to the modes of exercise [ 21 ]. For example, CrossFit training (a high-intensity mixed exercise model of concurrent strength and endurance performance) reduces lipid oxidation in obese individuals [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While physical activity (PA) has long been associated with a reduced risk of mortality and morbidity from chronic and degenerative diseases [16][17][18][19][20][21], the research interest on the role of PA on mental health has emerged more recently. PA has been related to an improvement in general well-being [22], enhanced perception of quality of life [23,24] and mood, as well as to a significant reduction in anxious and depressive symptomatology [25].…”
Section: Introductionmentioning
confidence: 99%